Workplace Contact and Support for Anti-Immigration Parties - Henrik Andersson; Sirus H. Dehdari (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
This paper studies the consequences of an increased presence of immigrants in the workplace on anti-immigration voting behavior by combining detailed Swedish workplace data with election outcomes for a large anti-immigration party (the Sweden Democrats). At each election precinct, we match the election outcomes with the share of non-European co-workers among the average native-born worker for three consecutive elections between 2006 and 2014. Using a fixed effects approach, we estimate a negative effect of an increased share of non-Europeans in the workplace on support for the Sweden Democrats: a one standard deviation increase in the average share of non-European co-workers decreases the precinct vote share for the Sweden Democrats by roughly 0.4 percentage points. We show that these results are solely driven by within-skill contact, and by contact within occupations that are less exposed to job loss. We interpret the results as supporting the contact hypothesis: that increased interactions with minorities r duce prejudice among native-born voters, which leads to lower support for anti-immigration parties.
Keywords: 330